2009
DOI: 10.1177/1049732309348365
|View full text |Cite
|
Sign up to set email alerts
|

Family Presence During Resuscitation and Invasive Procedures: The Nurse Experience

Abstract: The purpose of this study was to understand the experiences of nurses who participate with families during resuscitation and invasive procedures in the hospital. Seventeen nurses in a large metropolitan area in the northeastern United States were interviewed about their thoughts and feelings about participating with families during these procedures. Conversations were audiotaped and transcribed verbatim for analysis. Transcripts were analyzed using van Manen's technique of isolating thematic statements. Four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0
26

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 25 publications
2
58
0
26
Order By: Relevance
“…[8][9][10][11][12][13] Research reflects that families value receiving timely information in a transparent manner, comforting their loved one, and having closure when they are present during crisis events. 2,9,[14][15][16][17] Research with health professionals similarly suggests that family presence during resuscitation and invasive procedures helps families grasp the severity of life-threatening events, facilitates communication, supports grieving, allows families to see the efforts of the care team, and reduces litigation risk. 9,15,16,[18][19][20][21] Health professionals also perceive disadvantages, including performance anxiety of resuscitation teams, family disruptions of care, deleterious effects on family, compromised patient confidentiality, increased litigation risk, and family's desires to prolong futile resuscitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] Research reflects that families value receiving timely information in a transparent manner, comforting their loved one, and having closure when they are present during crisis events. 2,9,[14][15][16][17] Research with health professionals similarly suggests that family presence during resuscitation and invasive procedures helps families grasp the severity of life-threatening events, facilitates communication, supports grieving, allows families to see the efforts of the care team, and reduces litigation risk. 9,15,16,[18][19][20][21] Health professionals also perceive disadvantages, including performance anxiety of resuscitation teams, family disruptions of care, deleterious effects on family, compromised patient confidentiality, increased litigation risk, and family's desires to prolong futile resuscitation.…”
mentioning
confidence: 99%
“…2,9,[14][15][16][17] Research with health professionals similarly suggests that family presence during resuscitation and invasive procedures helps families grasp the severity of life-threatening events, facilitates communication, supports grieving, allows families to see the efforts of the care team, and reduces litigation risk. 9,15,16,[18][19][20][21] Health professionals also perceive disadvantages, including performance anxiety of resuscitation teams, family disruptions of care, deleterious effects on family, compromised patient confidentiality, increased litigation risk, and family's desires to prolong futile resuscitation. 9,[18][19][20][22][23][24][25] Research findings have not supported the disadvantages perceived by health professionals 17,19,26,27 ; therefore, major health organizations now encourage family presence during resuscitation.…”
mentioning
confidence: 99%
“…The difference in FPR-BS mean composite scores between the intervention and control groups was not statistically significant on the pretest (P = . 19) or posttest (P = .21).…”
Section: Perception Findingsmentioning
confidence: 99%
“…17 Research conducted with nurses and other health care providers has shown that FPDR increases family members' understanding and ability to make care decisions, improves emotional support for families and facilitates their grieving, and promotes professionalism among the members of the health care team. 18,19 Yet, despite patient and family support and positive findings regarding its outcomes, FPDR remains controversial and far from the norm in clinical practice. 1,[20][21][22][23] FPDR implementation in bedside care has been linked to nursing because patients and their family members are most likely to express their desires for FPDR to nurses.…”
mentioning
confidence: 99%
See 1 more Smart Citation